An elusive Neotropical giant, Hondurantemna chespiritoi gen. n. & sp. n. (Antemninae, Mantidae): a new lineage of mantises exhibiting an ontogenetic change in cryptic strategy - Rodrigues, Henrique M. (2017)
We present the description of a new genus and new species of praying mantis, Hondurantemna chespiritoi gen. n. & sp. n. This species of cryptic mantis, collected in National parks in Mexico and Honduras, remained unknown despite its considerable body size. Based on a phylogenetic analysis with molecular data and traditional morphological analysis, we place this new genus within Antemninae, a monotypic Mantidae subfamily. We update the subfamily concept for Antemninae and provide a key to the two genera. We describe the external morphology of immatures and adults of the new species as well as the genital complexes of both sexes and the ootheca of Antemna rapax. The observed morphological changes between immature and adult females suggests that the selection for an alternate strategy for crypsis is a response to size increase of the abdomen during development. Immatures exploit a stick/branch habitat based on their morphological appearance while adult females appear as a leaf to disguise the profile of the body.